(untitled) (Journal of Electrical, Electronics and Informatics, 2026)
In recent years, the evolution of electric power systems characterized by high integration of renewable energy sources (RES), distributed generation, and microgrids has introduced significant challenges in maintaining system stability, load management, and grid reliability. This review article, titled “Intelligent Fuzzy Logic Control for Next-Generation Power Systems: A Review of Applications in Stability, Load Management, and Renewable Integration”, provides a comprehensive synthesis of research from the last decade (≈2015–2025) on the use of fuzzy logic controllers (FLCs) in modern power systems. We systematically analysis studies involving FLC applications for frequency and voltage stability, load balancing, energy management in hybrid renewable systems (e.g., PV–wind–battery), and integration with advanced devices (e.g., converters, storage, FACTS). We discuss the evolution from classic type-1 FLC to adaptive, hybrid, and deeply integrated frameworks (e.g., fuzzy-self-tuned PID, neuro-fuzzy, deep-FLC), highlighting their strengths in handling nonlinearity and uncertainty, as well as limitations regarding rule complexity, real-time implementation, and scalability. The review identifies key trends, critical gaps especially in standardized performance benchmarking, real-world deployment, and coordination among multiple control layers and proposes a research roadmap for future work. Our findings aim to guide researchers and practitioners seeking to design intelligent control systems that support the reliability, efficiency, and resilience of next-generation power grids.